Harvest for hope : a guide to mindful eating / Jane Goodall with Gary McAvoy and Gail Hudson. - Goodall, Jane, 1934- (Warner Wellness, 2006)
"An exploration of the global meaning of food and what all of us can do to exercise power over the food industry and, ultimately, our environment"--Provided by the publisher.